Insomnia as a path to alcoholism: tolerance development and dose escalation. Issue 8 (12th May 2018) - Roehrs, Timothy; Roth, Thomas
Abstract: Study Objectives: To assess the risks associated with the use of alcohol as a "sleep aid, " we evaluated tolerance development to pre-sleep ethanol's sedative-hypnotic effects, and subsequent ethanol dose escalation. Methods: Volunteers, 21–55 years old, with insomnia in otherwise good medical and psychiatric health and no history of alcoholism or drug abuse participated. In experiment 1 ( n = 24) 0.0, 0.3, or 0.6 g/kg ( n = 8 per dose) ethanol was administered before sleep and 8-hour nocturnal polysomnograms (NPSGs) were collected. In experiment 2, after six nights pretreatment with ethanol 0.45 g/kg ( n = 6) versus placebo ( n = 6), choice of pre-sleep ethanol or placebo was assessed over seven choice nights. Results: The 0.6 g/kg ethanol dose increased total sleep time and stage 3–4 sleep on night 2, but these effects were lost by night 6 ( p < .05). Six nights of ethanol pretreatment produced on the choice nights more self-administered ethanol refills than the placebo pretreatment ( p < .03). Conclusions: These are the first data to explicitly show the risks associated with the use of alcohol as a "sleep aid" among people with insomnia. Initially, a moderate dose of ethanol improved NPSG sleep, which was lost by night 6. Tolerance was associated with enhanced self-administration of pre-sleep ethanol.